In the shadow of nation-states. Silesia divided (1918-1945) - Wiszewski, Przemysław (Publishing House eBooki.com.pl, 2014)
The book is the 4th volume from of the Cuius Regio series. It comprises articles devoted to the cohesion of Silesia as a region in the years 1918-1945. During this period Silesia was partitioned among three nation-states (Czechoslovakia, Germany and Poland). As in all volumes of the series, chapters in the book present research on administrative structures (Kruszewski), economy (Urbaniak), social groups (Przerwa), ethnic and national issues (Strauchold), and regional identity (Linek) as factors and forces both strengthening and weakening regional cohesion. A general outline of the relevant part of the region’s history shows conditions under which deep changes occurred in a relatively short period of time affecting every field of Silesians’ lives.
Keywords: Cuius Regio project; nation-states; region; Silesia